Insectos del frijol almacenado y su control - Franco, T.L. (Centro Internacional de Agricultura Tropical (CIAT), Centro de Información sobre Frijol, 1986)
The biology of the main stored bean pests (Zabrotes subfasciatus and Acanthoscelides obtectus), their control at the small-farmer (cultural control and use of vegetable oils and ash) and commercial levels (disinfestation and protection), and control by var. resistance are briefly analyzed. Color photos are included. (CIAT)